Pengaruh Profitabilitas, Struktur Aktiva, Resiko Bisnis, dan Ukuran Perusahaan Terhadap Struktur Modal - Rahmiati, Rahmiati; Fitra, Halkadri; Grizmaldy, Fastri Prisma (Jurnal Kajian Manajemen Bisnis, 2017)
The purpose of this research is to examine the effect of profitability, asset structure, business risk, and firm size to capital structure. The research populations are 44 mining companies which listed In Indonesian Stock Exchange (IDX) with 11 research samples around 2011-2015. This research used purposive sampling method. The statistical methods used in this research are multiple regressions. The result shows that insignificant effect of profitability, business risk, and firm size to capital structure andÂ  positive significant effect of asset structure to capital structure. Â Keywords: Profitability, Asset Structure, Business Risk, Firm size, Capital Structure